The impact of persistent precarity on patients’ capacity to manage their treatment burden: A comparative qualitative study between urban and rural patients with multimorbidity in South Africa - van Pinxteren, Myrna; Mbokazi, Nonzuzo; Murphy, Katherine; Mair, Frances S.; May, Carl; Levitt, Naomi (Frontiers in Medicine, 2023)
Background: People living with multimorbidity in low- and middle-income countries (LMICs) experience a high workload trying to meet the demands of self-management. In an unequal society like South Africa, many people face continuous economic uncertainty, which can impact on their capacity to manage their illnesses and lead to poor health outcomes. Using precariousness – the real and perceived impact of uncertainty – as a lens, this paper aims to identify, characterize, and understand the workload and capacity associated with self-management among people with multimorbidity living in precarious circumstances in urban and rural South Africa. Methods: We conducted qualitative semi-structured interviews with 30 patients with HIV and co-morbidities between February and April 2021. Patients were attending public clinics in Cape Town (Western Cape) and Bulungula (Eastern Cape). Interviews were transcribed and data analysed using qualitative framework analysis. Burden of Treatment Theory (BoTT) and the Cumulative Complexity Model (CuCoM) were used as theoretical lenses through which to conceptualise the data. Results: People with multimorbidity in rural and urban South Africa experienced multi-faceted precariousness, including financial and housing insecurity, dangerous living circumstances and exposure to violence. Women felt unsafe in their communities and sometimes their homes, whilst men struggled with substance use and a lack of social support. Older patients relied on small income grants often shared with others, whilst younger patients struggled to find stable employment and combine self-management with family responsibilities. Precariousness impacted access to health services and information and peoples’ ability to buy healthy foods and out-of-pocket medication, thus increasing their treatment burden and reducing their capacity. Conclusion: This study highlights that precariousness reduces the capacity and increases treatment burden for patients with multimorbidity in low-income settings in South Africa. Precariousness is both accumulative and cyclic, as financial insecurity impacts every aspect of peoples’ daily lives. Findings emphasise that current models examining treatment burden need to be adapted to accommodate patients’ experiences in low-income settings and address cumulative precariousness. Understanding treatment burden and capacity for patients in LMICs is a crucial first step to redesign health systems which aim to improve self-management and offer comprehensive person-centred care.